Modern literary Nepali an introductory reader - Hutt, Michael (Michael J.) (Delhi Oxford University Press, 1997)
On Nepali grammar with selected 20th century Nepali poetry with English translation.
Keywords: Nepali language -- Grammar; Nepali poetry -- Translations into English